2021
DOI: 10.1088/1361-6668/ac211f
|View full text |Cite
|
Sign up to set email alerts
|

A numerical method for spatially-distributed transient simulation to replicate nonlinear ‘defect-irrelevant’ behaviors of no-insulation HTS coil

Abstract: This paper presents a numerical method, based on the partial element equivalent circuit (PEEC) technique, for spatially-distributed and time-varying simulation to analyze nonlinear ‘defect-irrelevant’ behaviors of a no-insulation (NI) high temperature superconductor (HTS) coil. We suggest a resistivity parameterization approach in combination of the PEEC method to replicate electromagnetic dynamics of an NI HTS coil containing multiple ‘defects.’ The proposed method is adopted to investigate ‘defect-irrelevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…For instance, quench detection, magnet diagnostics, and instrumentation techniques [2][3][4][5][6][7][8][9][10][11][12][13][14] have been considerably studied to investigate NI REBCO magnet quench. As a result, various quench simulation models [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] have been proposed, and it has been demonstrated that they are practicable in replicating quench voltage and the corresponding current distribution to some degree. However, these simulations still struggle to reproduce module coil voltages during quench in high magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, quench detection, magnet diagnostics, and instrumentation techniques [2][3][4][5][6][7][8][9][10][11][12][13][14] have been considerably studied to investigate NI REBCO magnet quench. As a result, various quench simulation models [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] have been proposed, and it has been demonstrated that they are practicable in replicating quench voltage and the corresponding current distribution to some degree. However, these simulations still struggle to reproduce module coil voltages during quench in high magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…The no-insulation (NI) winding technique [24] provides HTS coils with better thermal stability [25,26], higher current density [27,28], defect-irrelevance properties [29,30] and better mechanical integrity [31][32][33][34][35]. In recent years, the NI winding technique has facilitated quite a few breakthroughs in HTS magnet technology [28,36].…”
Section: Introductionmentioning
confidence: 99%
“…Charge-discharge cycles are performed at different ramp rates, up to 5 A/s, as well as fast discharge tests. Compared to the results reported in [13], where the same coil was operated in a liquid nitrogen bath, in this work the tests are carried out with conduction cooling, at temperatures between 4.7 K and 80 K. The coil electromagnetic behavior is assessed by measuring the magnetic field produced in its bore and the voltage signal acquired at the coil ends. The measurements are also used to retrieve, by means of a simplified lumped parameter circuit, some useful effective parameters, such as the longitudinal and radial resistances, from which the fraction of operating current flowing radially throughout the winding is estimated.…”
Section: Introductionmentioning
confidence: 99%